Evaluation of Hedege Fund Performance - Zhang, Qi (2007)
This paper provides a comprehensive analysis of the risk-return characteristics of hedge funds and market indexes, portfolio allocation involving hedge funds, and risk exposure of various hedge fund strategies. In general, hedge funds outperform market indices in terms of higher mean excess return, lower standard deviation, and better Sharpe ratio. Beside, hedge funds exhibit low correlation to market indexes suggesting great opportunities for diversification. In a mean-variance framework, I find that a combination of hedge fund strategies and passive indexing provides significant better risk-return tradeoff than investing solely in passive asset classes. Finally, using multi-factor CAPM and stepwise regression, I find that the set of market factors captures a large percentage of the hedge fund return characteristics , and the risk exposures to hedge fund strategies are quite different in general, meanwhile, most strategies have significant factor loading on Russell 3000, Lehman High Yield, and Large-Small factor.